Cultural Analysis of Persian Proverbs Including 'EYE' as Sensory Organ and 'SEE' as Perception Verb - Arezoo Sharifrad (Universitas Muhammadiyah Barru, 2024)
This study investigates how much the sensory body organ ‘eye’ is linked to the corresponding perception verb ‘see’ in Persian embodiment proverbs. It aimed to provide a quantitative and qualitative analysis of the Persian proverbs and their equivalents in English. This research utilized the conceptual metaphor theory proposed by Lakoff and Johnson. Data were collected from the Persian Dictionary of Proverbs and were analyzed to determine the frequency, speech act functions, and framing in these proverbs. Data analysis revealed that Persian proverbs are framed more around gain-framing and loss-framing rather than avoidance-framing. Most Persian proverbs function as statements and complaints rather than advice or warnings. The results showed that proverbs involving 'eye' and 'see,' surpassed others related to ‘eye’ and ‘blind’, and the frequency number of the perception verb ‘see’ was more than the sensory body organ ‘eye’. Finally, despite variations in the use of different words that are used with eye or see in a single proverb, this study concludes that the ‘eye’ is more used with its allocated perception verb ‘see’. However, the perception verb ‘see’ is never used with ‘blind’, but ‘eye’ is often used with ‘blind’.